Erigeron breviscapus (Vant.) Hand-Mazz.: A Promising Natural Neuroprotective Agent for Alzheimer’s Disease - Dong, Xiaoyu; Qu, Shengtao (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is the most common neurodegenerative disease and is characterized by progressive cognitive dysfunction and memory loss in the elderly, which seriously affects the quality of their lives. Currently, the pathogenesis of AD remains unclear. Molecular biologists have proposed a variety of hypotheses, including the amyloid-β hypothesis, tau hyperphosphorylation hypothesis, cholinergic neuron injury, inflammation caused by an abnormal immune response, and gene mutation. Drugs based on these pathological studies, including cholinesterase inhibitors and N-methyl-D-aspartate receptor antagonists, have achieved a certain level of efficacy but are far from meeting clinical needs. In the recent years, some important advances have been made in the traditional Chinese medicine treatment of AD. Erigeron breviscapus (Vant.) Hand-Mazz. (EBHM) is an important medicinal plant distributed in Yunnan Province, China. Studies have shown that EBHM and its active ingredients have a variety of pharmacological effects with good therapeutic effects and wide application prospects for cognitive disability-related diseases. However, to our best knowledge, only few review articles have been published on the anti-AD effects of EBHM. Through a literature review, we identified the possible pathogenesis of AD, discussed the cultivation and phytochemistry of EBHM, and summarized the pharmacological mechanism of EBHM and its active ingredients in the treatment of AD to provide suggestions regarding anti-AD therapy as well as a broader insight into the therapeutic potential of EBHM.